Swelling behavior and diffusion studies of high-water-retaining acrylamide/potassium methacrylate hydrogels - Mohan, Y. M.; Murthy, P. S. K.; Rao, K. M.; Sreeramulu, J.; Raju, K. M. (Journal of Applied Polymer Science, 2005)
Poly(acrylamide-co-potassium methacrylate) hydrogels were prepared by free-radical simultaneous polymerization with aqueous solutions of acrylamide (AAm) and potassium methacrylate (KMA) with a redox initiator. The copolymerization was performed with eight different compositions of KMA at a fixed concentration of oil-soluble crosslinkers, including 1,4-butanediol diacrylate and ethylene glycol dimethacrylate (EGDMA). For every composition of AAm/KMA copolymer, the percentage swelling, swelling equilibrium, and diffusion characteristics were investigated. The copolymers were further studied for deswelling properties. The power law relationships of the hydrogels were evaluated for variation in terms of saline concentration. The AAm/KMA copolymers were confirmed by IR spectroscopy. Thermal studies of hydrogels were performed with differential scanning calorimetry and thermogravimetric analysis. EGDMA was found to be a better crosslinker for obtaining higher swelling and deswelling properties for the AAm/KMA hydrogels. (c) 2005 Wiley Periodicals, Inc.
Keywords: Diffusion; hydrogels; swelling

Influence of film structure on mobilities of charge carriers in conducting polymers - Harima, Yutaka; Jiang, Xiaoqing; Patil, Rahul; Komaguchi, Kenji; Mizota, Haruo (Electrochimica Acta, 2007)
Two sorts of poly(3-hexylthiophene) (PHT) films with the same chemical compositions were prepared, and their electrochemical, spectroscopic, and transport properties were studied with a special interest in a possible influence of film structure on mobilities of charge carriers. One of the PHT films was electrochemically synthesized using 3-hexylthiophene as a monomer (as-grown film) and the other was obtained by dissolving the as-grown film in chloroform and then casting the polymer solution (cast film). A clear difference was observed in the mobility versus doping level plot between the two sorts of PHT films, demonstrating that the difference is caused only by a distinction in film structure. An initial decreasing feature of the mobility plot observed for the cast films was accounted for in terms of swelling of the films at an early stage of doping. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Doping; electrosynthesis; mobility; poly(3-hexylthiophene); swelling

Transport study on as-grown and cast films of electrogenerated poly(3-hexylthiophene) - Jiang, Xiaoqing; Harima, Yutaka; Patil, Rahul (Materials Letter, 2007)
Two kinds of poly(3-hexylthiophene) films with identical chemical compositions are prepared. One of the films is obtained by electropolymerization of 3-hexylthiophene (as-grown film) and the other is prepared by casting a solution dissolving the as-grown film (cast film). A clear difference is found in the mobility vs. doping level plots between the as-grown and cast films and its reason is discussed. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: mobility; poly(3-hexylthiophene); swelling; thin film; transport mechanism

Self assembled hydrophobic nanoclusters of poly(methylmethcrylate) embedded into polyvinyl alcohol based hydrophilic matrix: preparation and water sorption study - Shukla, Sandeep Kumar; Shaikh, A. Wasif; Gunari, Nikhil; Bajpai, A. K.; Kulkarni, R. A. (Journal of Applied Polymer Science, 2009)
Hydrophilic matrices containing nanosized Clusters of hydrophilic moieties have demonstrated potential applications in biomedical field. A novel hydrogel containing nanosized domains (20-35 nm) of hydrophobic moieties of poly(methyl methacrylate) (PMMA) was prepared by grafting crosslinked p ly(acrylic acid-co-methyl-methacrylate) chains onto polyvinyl alcohol (PVA) backbone using an efficient redox system. The graft copolymerization process was investigated to observe the influence of gel components on the kinetic parameters of grafting such as rate of grafting (R(g)), grafting yield (G(y)) and grafting efficiency (G(e)). The prepared graft nanohydrogel was evaluated for its water sorption potential under varying chemical composition of the gel and changing pH, temperature, and ionic strength of the swelling bath. The swelling process was also examined mechanistically and diffusion constants (D) of water molecules through the swellable nanohydrogel were also evaluated. (c) 2008 Wiley Periodicals, Inc. J ppl Polym Sci 111: 1300-1310, 2009
Keywords: graft copolymers; hydrophilic polymers; Nanocomposites; swelling

Free radical graft copolymerization of N-vinyl-2-pyrrolidone onto k-carrageenan in aqueous media and applications - Mishra, Madan Mohan; Sand, Arpit; Mishra, Dinesh Kumar; Yadav, Mithilesh; Behari, Kunj (Carbohydrate Polymers, 2010)
In the present article, the graft copolymer of k-carrageenan with N-vinyl-2-pyrrolidone (NVP) has been synthesized using PMS/maleic acid as a redox initiator in aqueous medium and reaction conditions have been optimized to obtain maximum % grafting ratio (%G). The optimum conditions of maximum grafting have been found by varying the different parameters. On increasing the concentration of maleic acid and peroxymonosulphate from 1.6 x 10(-3) to 4.8 x 10(-3) mol dm(-3) and 0.6 x 10(-2) to 2.2 x 10(-2) mol dm(-3) respectively, the initially grafting parameters increased and after a certain range of concentration grafting parameters showed decreasing trend. The small increment of concentration in hydrogen ion causes increment in percentage grafting. It was observed that the grafting parameters increase as the concentration of N-vinyl-2-pyrrolidone increases up to 16 x 10(-2) mol dm(-3) after that it decreased. The optimum condition for maximum grafting has obtained at concentration 1.0 g dm(-3) of k-carrageenan at 40 degrees C and 120 min, respectively. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: flocculation; Graft copolymer; k-Carrageenan; Metal ion uptake; N-vinyl-2-pyrrolidone; swelling

Alginic acid-g-poly(N-vinylformamide) graft copolymer: synthesis, characerization, swelling, and flocculation property - Sand, Arpit; Yadav, Mithilesh; Mishra, Dinesh Kumar; Behari, Kunj (Journal of Applied Polymer Science, 2011)
The graft copolymer of N-vinylformamide with alginic acid was synthesized by free radical polymerization using potassium peroxymonosulphate and thiourea as redox pair in inert atmosphere. The optimum conditions for maximum grafting have been determined by varying the concentrations of N-vinylformamide, potassium peroxymonosulphate, thiourea, sulfuric acid, alginic acid as well as time duration and temperature. The grafting parameters increase up to the certain concentrations of N-vinylformamide, potassium peroxymonosulhate, thiourea, and hydrogen ion while thereafter grafting parameters decrease. The effect of alginic acid concentration on grafting parameters has been observed to decrease continuously. It has also been found that grafting parameters increase up to certain time and temperature, respectively, and thereafter decrease. The swelling properties of graft copolymer in terms of swelling ratio and percent swelling are investigated. Flocculation property of pure and grafted sample for both coking and noncoking coals is also investigated for the treatment of coal mine waste water. The graft copolymer has been characterized by Fourier transform infrared spectroscopy as well as thermogravimetic analysis. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 121: 1400-1407, 2011
Keywords: alginic acid; flocculation; Graft copolymer; N-vinylformamide; swelling

Design and development of trivalent aluminum ions induced self healing polyacrylic acid novel hydrogels - Anjum, Sadiya; Gurave, Pramod; Badiger, Manohar V.; Tiwari, Neha; Gupta, Bhuvanesh (POLYMER, 2017)
Development of ionically crosslinked superabsorbent polyacrylic acid (PAA) self-healing hydrogels using trivalent aluminum ions was investigated. The PAA hydrogels exhibited excellent self-healing behavior depending on the amount of the aluminum within the matrix. The migration of these ions within the polymer matrix was responsible for the physical crosslinking of the hydrogel and the origin of self healing ability. The PAA-Al hydrogels were insoluble in water and exhibited significantly high degree of swelling (similar to 4000%). Hydrogel also exhibited good mechanical properties with high level of elongation. Excellent self-healing efficiency was observed under dynamic as well as oscillatory Theological measurements. The presence of Al ions within PAA hydrogel facilitated the self-healing ability because of the ionic interaction in these gels which plays the key role of dynamic reversible sacrificial bonds which reforms upon reversal of the deformative force. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Aluminum chloride; Behavior; Complex; Composite; crosslinking; Delivery; High-Mechanical Strength; hydrogels; Network; Polyacrylic acid; Polymeric Materials; Self-healing; swelling; Tough; pH

Polymeric PEI/PEG coated optical fiber fabry-perot interferometer for CO2 detection - Pawar, Dnyandeo; Lo Presti, Daniela; Lemma, Enrico D.; Rainer, Alberto; Kumar, Ajay; Kanawade, Rajesh; Silvestri, Sergio; Schena, Emiliano; Massaroni, Carlo (IEEE Sensors Journal, 2024)
Monitoring carbon dioxide (CO2) gas is essential for numerous applications, but the detection of CO2 in miniaturized devices presents significant challenges. In this study, a polyethyleneimine/poly(ethylene glycol) (PEI/PEG) coated optical fiber Fabry-Perot interferometer (FPI) and its charge transfer process toward CO2 are investigated. Scanning electron microscopy and Fourier transform infrared spectroscopy were used to analyze the surface morphology and vibration bands of the PEI/PEG composite. The PEI/PEG composite Fabry-Perot (FP) cavity of length similar to 13 mu m is coated at the distal end of the single-mode fiber using a dip coating technique. A highly sensitive optical and low-cost FPI probe fabrication has displayed a linear sensitivity of 17.10 nm/% in the range of 0.31%-1.25% CO2 gas. The response and recovery times of the sensor are in a few tens of seconds. The enhanced performance of the sensor is primarily due to the protonation and charge transfer between CO2 gas molecules and PEI/PEG composite. Due to low-cost fabrication and high sensitivity, this FPI sensor can be used in a range of potential applications in bioprocessing, healthcare, and environmental monitoring.
Keywords: dip coating; Fresnel's reflection; Interference; monitoring; Optical fiber sensors; Optical fibers; polymer composite; Polymers; refractive index; sensitivity; Sensor phenomena and characterization; sensors; swelling; Temperature sensors